Pengaruh Leverage, Ukuran Perusahaan Dan Tingkat Pengembalian Aset Terhadap Nilai Perusahaan Pada Pt Sumber Alfaria Trijaya Tbk Periode 2013-2023 (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2025)
This study aims to determine the effect of Leverage, Firm Size, and Return on Assets on Firm Value at PT Sumber Alfaria Trijaya Tbk for the 2013–2023 period. This study uses a quantitative approach with secondary data in the form of annual financial reports. The analytical techniques used include descriptive statistical analysis, classical assumption testing, multiple linear regression, and hypothesis testing. The results of the partial regression analysis indicate that Leverage has no significant effect on firm value, with a calculated t value of -2.115 < t table 2.36462 and a significance value of 0.072 > 0.05. Firm size has a positive and significant effect on firm value, with a calculated t value of 3.495 > t table 2.36462 and a significance value of 0.010 > 0.05. Return on Assets also has a positive and significant effect on firm value, with a calculated t value of 2.737 > t table 2.36462 and a significance value of 0.029 > 0.05. Simultaneously, the variables Leverage, Company Size, and Return on Assets have a significant effect on company value. This is indicated by the calculated f value of 42.925 > ttable 4.35 with a significance value of 0.000 < 0.05. The coefficient of determination (R²) value is 0.948, which means that 94.8% of the variation in company value can be explained by these three independent variables, while the remaining 5.2% is explained by other variables outside this research model.